THE INFLUENCE OF CURRENT RATIO, RETURN ON ASSET, DEBT TO EQUITY RATIO AND GOOD CORPORATE GOVERNANCE ON MARKET VALUE ADDED (EMIPICAL STUDY ON BASIC INDUSTRY AND CHEMICAL COMAPNIES LISTED ON INDONESIA STOCK EXCHANGE) - Sigit Mareta; Wahyu Anggraini (Universitas Mercu Buana, 2021)
The purpose of this research is to determine the influence of Current Ratio, Return on Asset, Debt to Equity ratio and, Good Corporate Governance on Market Value Added. The population used in this study is the basic industry and chemical companies listed on the Indonesia Stock Exchange within 2014-2016 with a total of 25 companies. The research used purposive sampling method. The method of purposive sampling and regression analysis logistics, are use for election sample. The variable Market Value Added and Good Corporate Governance are measured by dummy and other variables as CR, ROA and DER measured by the ratio.The results show that current ratio and debt to equity ratio has a significant influence on Market Value Added, while Return on Assets and Good Corporate Governance doesn't.